A comparative study of the ammonia-nitrogen and phosphorus load of extensive and semi-intensive shrimp pond effluents. - Gonzales, Myla C. (1994.)
This study was conducted to compare the levels of ammonia nitrogen and reactive phosphorus in the effluents of the extensive and the semi-intensive ponds (during the 120 day culture period) at the Brackiswater Aquaculture Center of the University of the Philippines in the Visayas, College of Fisheries, Leganes. An extensive shrimp pond with 33,000 fry per hectare and a 86,000 fry per hectare semi-intensive pond was utilized in this study. Strickland and Parson (11972) method was used in analyzing water samples., Results showed that during the harvest period the phosphorus effluent level and ammonia-nitrogen level is high in semi-intensive pond compared to the extensive pond. Analysis of variance, Two by Three Factorial Experiment in CRD Method, showed no significant difference in ammonia-nitrogen levels both between the two culture systems and the three sampling periods (start, middle and harvest). Reactive phosphorus a significant difference both between the disparate culture system and the three sampling periods. It further showed that the highest mean level of ammonia-nitrogen and phosphorus is well within the prescribed level of being a clean water by the water quality standard and does not meet the measured level of coastal water quality standard as a polluted water.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Shrimp Ponds -- Ammonia-Nitrogen.; Shrimp Ponds -- Phosphorus Load